Issues and Challenges for Bulk‐Type All‐Solid‐State Rechargeable Lithium Batteries using Sulfide Solid Electrolytes. Issue 5 (23rd January 2015) - Jung, Yoon Seok; Oh, Dae Yang; Nam, Young Jin; Park, Kern Ho
Abstract As lithium rechargeable batteries are considered a potential candidate for large‐scale energy storage applications in devices such as electric vehicles (EVs) and smart grids, their safety has become of prime concern. This calls for the need to replace the flammable organic liquid electrolyte (LE) with an inorganic solid electrolyte (SE), and thus, develop bulk‐type all‐solid‐state lithium batteries (ASLBs), fabricated using a scalable process. Sulfide SEs are considered the most competitive candidate owing to their high conductivity at room temperature (10−3–10−2 S cm−1), which is comparable to that of LEs, and their ductility, which enables the fabrication of ASLBs simply using cold pressing. In the present review, issues and challenges to be faced for the fabrication of bulk‐type ASLBs using sulfide SEs are presented and discussed, with a special focus on the development of SEs, compatibility of the electrode materials with SEs, and structure of the composite electrodes. Recent progress made with the aim of addressing the aforementioned issues and challenges is also presented, to provide an outlook on the future of SEs and ASLBs.